2017
DOI: 10.3390/ijerph15010018
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Infant Mortality by Age and Season of Birth, 1800–1899: Did Season of Birth Affect Children’s Chances for Survival?

Abstract: This paper focuses on the influence of season of birth on infant mortality among the Sami and non-Sami populations in northern Sweden during the nineteenth century. The source material is a set of data files from the Demographic Data Base at Umeå University, making it possible to combine age at death (in days), month of death, and month of birth over the course of the entire century. Cox regression models reveal that for the first week of life, season of birth had no influence on the risk of mortality. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…We previously showed that the season of birth indicated differential effects depending on age at death among Sami populations in the parishes of Jokkmokk and Jukkasjärvi in Swedish Sápmi [25]. Being born during winter was related to a higher risk of neonatal mortality, while being born during summer was related to a higher risk of mortality after 6 months of age [25]. These results implied that infant mortality risks are generally higher during winter and are also related to sensitive stages during the first year of life, both as new-borns during the neonatal period and around the age of six months when food was introduced in combination with the waning effect of maternal antibodies.…”
Section: Season Of Birth and Infant Mortalitymentioning
confidence: 96%
See 2 more Smart Citations
“…We previously showed that the season of birth indicated differential effects depending on age at death among Sami populations in the parishes of Jokkmokk and Jukkasjärvi in Swedish Sápmi [25]. Being born during winter was related to a higher risk of neonatal mortality, while being born during summer was related to a higher risk of mortality after 6 months of age [25]. These results implied that infant mortality risks are generally higher during winter and are also related to sensitive stages during the first year of life, both as new-borns during the neonatal period and around the age of six months when food was introduced in combination with the waning effect of maternal antibodies.…”
Section: Season Of Birth and Infant Mortalitymentioning
confidence: 96%
“…Seasonality, neonatal mortality, and stillbirths Previous research of neonatal mortality in Swedish Sápmi has revealed that Sami infants born during the summer months (July and August) had the highest neonatal mortality risk, whereas the non-Sami infants showed no seasonal differences [7]. We previously showed that the season of birth indicated differential effects depending on age at death among Sami populations in the parishes of Jokkmokk and Jukkasjärvi in Swedish Sápmi [25]. Being born during winter was related to a higher risk of neonatal mortality, while being born during summer was related to a higher risk of mortality after 6 months of age [25].…”
Section: Season Of Birth and Infant Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…From previous research on infant mortality in historical populations, we know that the season of birth affects the risk of infant mortality and season of birth is, therefore, a good proxy for living conditions in utero and during early infancy [8,12]. Neonatal mortality also appears to be associated with the seasonality of infectious diseases and extreme temperatures, e.g.…”
Section: The Impact Of Weather On Neonatal Mortalitymentioning
confidence: 99%
“…Generally, the infant mortality rate was higher among the Sami population compared to the non-Sami population until 1860, after which the differences decreased over time [5]. Comparing seasonal patterns of neonatal mortality during the nineteenth century, the mortality rate was higher during the winter for Sami and non-Sami populations [8]. How these seasonal patterns changed over time and in relation to temperature differences during the winter is still unknown.…”
Section: Introductionmentioning
confidence: 99%